Defect‐related mechanism of ferromagnetic behaviors for ZnCoO:H films formed by PLD with bias voltage application. Issue 10 (12th August 2013) - Sasaki, Kazuma; Komiyama, Takao; Chonan, Yasunori; Yamaguchi, Hiroyuki; Aoyama, Takashi; Chauveau, Jean‐Michel; Sallet, Vincent; Morhain, Christian; Feuillet, Guy
Abstract Ferromagnetic behaviors of Co‐doped ZnO films were investigated by using pulsed laser deposition (PLD) with the bias voltage application technique and by changing the partial pressure of oxygen ambient. The 50 V change in the PLD bias voltage caused the oxygen to zinc (O/Zn) ratio in the film to change by about 7%. Ferromagnetic behaviors were observed after the hydrogenation process. As the the O/Zn ratio in the ZnCoO:H films deviated more from the stoichiometric condition, the saturation magnetization (Ms) significantly decreased but sometimes increased. On the other hand, the deviation from the stoichiometric condition (that is the increase in the native defect concentration) significantly changed the carrier concentration. As the carrier concentration (Fermi level) increased, Ms increased first, then decreased, and finally increased again. Thus, the native defects certainly affected the Ms, but only through the shift of the Fermi level.